THE ROLE OF TAX IDENTIFICATION NUMBER IN TAX FRAUD PREVENTION : APPLIED RESEARCH AT THE GENERAL TAX AUTHORITY IN IRAQ (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This thesis aims to show the effects of the development of the traditional manual system of the tax accounting process to the electronic system by the activation of the tax identification numbers (TINs) mechanism. The impact of this development is facilitating the tax accounting process, tax fraudand thus increasing the tax outcome.To prove the research hypothesis, an electronic system was designed based on income tax report, estimation note of individuals, in additional to using Adobe Dreamweaver application to write PHP, HTML, Javascript, and CSS web languages to implement  the proposed system. The research reached a set of conclusions, the most important of which is; not enough the communication methods between the General Tax Authority and its branches analogy on to the volume of work and the speed required in its completion, and there is no information network between the authority and state departments. The research recommends a set of recommendations, the most important of which are; The necessity of linking the General Authority for Taxes with all its branches and all state departments with an electronic information network to provide the General Authority for Taxes with information about the taxpayers, especially those who are not previously registered with the Authority.